STUDENTS’ PERCEPTIONS OF THE IMPLEMENTATION OF DIALOGIC TEACHING FOR IMPROVING SPEAKING SKILLS AT A UNIVERSITY IN WEST JAVA - Romios, Laser; Musthafa, Bachrudin; Lengkanawati, Nenden Sri (English Review: Journal of English Education, 2024)
In the present day, English has become a crucial language that individuals must acquire proficiency in. It has been extensively taught as a second language in many locations throughout the globe for a considerable period of time. In the Indonesian context, the tertiary students seem to still lack of English skills despite prolonged duration of learning English. Therefore, an effective teaching strategy is needed to teach English to tertiary students for the best outcomes possible. An experimental study to investigate whether Dialogic Teaching strategy works well to improve English speaking skills was conducted at a university in West Java. In particular, this study reveals the students’ perceptions of the implementation of Dialogic Teaching in a speaking class through the use of focus group discussion involving six participants of low, medium and high speaking skills in English. A qualitative analysis was conducted and some findings were found, including: (1) students being more motivated when under pressure; (2) students earning confidence boost; (3) students acquiring creativities in presenting ideas; (4) students engaging in a dialogic discussion; (5) students wanting a balanced classroom activity; and (6) students aspiring to have outdoor learning activities.Keywords: Dialogic teaching; Perception; Speaking class; Speaking skills; Tertiary Education;